Receptor-Ligand Interaction Mediates Targeting of Endothelial Colony Forming Cell-derived Exosomes to the Kidney after Ischemic Injury. Issue 1 (December 2018) - Viñas, Jose; Spence, Matthew; Gutsol, Alex; Knoll, William; Burger, Dylan; Zimpelmann, Joseph; Allan, David; Burns, Kevin
Abstract Endothelial colony forming cell (ECFC)-derived exosomes protect mice against ischemic kidney injury, via transfer of microRNA-(miR)-486-5p. Mechanisms mediating exosome recruitment to tissues are unclear. We hypothesized that ECFC exosomes target ischemic kidneys, involving interaction between exosomal CXC chemokine receptor type 4 (CXCR4) and stromal cell-derived factor (SDF)-1α. Ischemia-reperfusion was induced in mice by bilateral renal vascular clamp, with intravenous infusion of exosomes at reperfusion. Optical imaging determined exosome biodistribution, and miR-486-5p was measured by real-time PCR. Human umbilical vein endothelial cells (HUVECs) were cultured to study the CXCR4/SDF-1α interaction. Targeting of administered exosomes to ischemic kidneys was detected 30 min and 4 hrs after reperfusion. Exosomes increased miR-486-5p levels only in kidneys, within proximal tubules, glomeruli, and endothelial cells. Uptake of fluorescently-labeled exosomes into HUVECs, and exosomal transfer of miR-486-5p were enhanced by hypoxia, effects blocked by neutralizing antibody to SDF-1α or by the CXCR4 inhibitor plerixafor. Infusion of ECFC exosomes prevented ischemic kidney injuryin vivo, an effect that was not observed when exosomes were pre-incubated with plerixafor. These data indicate that ECFC exosomes selectively target the kidneys after ischemic injury, with rapid cellular transfer of miR486-5p. Targeting of exosomes may involve interaction of CXCR4 with endothelial cell SDF-1α.